Prague inbred lines of chickens: a biological model for MHC research - Plachý, J; Vilhelmová, M; Karakoz, I; Schulmannová, J (Folia biologica, 1989)
Evidence for further complexity of the genetic structure of chicken major histocompatibility complex (B) is reviewed, with a historical account showing mutual dependence of the development of an animal genetic model and the growth of scientific knowledge concerning the chicken MHC.
Keywords: křížení genetické; biologické modely; kur domácí; chov; Chickens; Breeding; Major Histocompatibility Complex; Models, Biological; hlavní histokompatibilní komplex; Crosses, Genetic; Animals; zvířata